Effects of Financial, Social, and Human Capital on Entrepreneurial Success: Evidence from Kathmandu Valley - Yadav, Maheshwar Prasad (Economic Journal of Nepal, 2022)
Nepal’s energy sector comprises both successful and subsistence entrepreneurs. In this connection, the enduring question arises of how successful entrepreneurs have something special in the context of the solar companies in Nepal. The purpose of this paper is to analyze the effects of financial capital, social capital, and human capital on entrepreneurial success in this sector of Nepal. The study adopts a causal-comparative research design to determine the effect of initial investment, access to finance, network ties, trust, shared vision, education, and experience on entrepreneurial success. This study is based on primary data that were collected from a sample of 102 owners/managers of 45 solar companies using a structured questionnaire. The factors affecting entrepreneurial success were determined by estimating the econometric models and correlation analysis using IBM SPSS Statistics 20. The results show that access to finance, network ties, trust, education, and experience appeared to be the major factors affecting entrepreneurial success. Factors like initial investment and shared vision did not appear to be the important factors affecting entrepreneurial success. Policy implications and future avenues were also discussed.